Impact of an educational intervention on the level of knowledge of sexually transmitted infections in adolescents of an educational institution of Huancayo 2017-2018 - Maldonado Gómez, Cesar Augusto (2020)
Introduction: sexually transmitted infections are considered a global public health problem and it is considered an epidemic that reaches the whole world. Objective: evaluate the results of an educational intervention on the knowledge of prevention of infections sexually transmitted in adolescents. Material and Methods: is a study experimental educational intervention type pre before/after no group control, the students of the institution educational Chinchaysuyo of the District of Sapallanga - Huancayo, Junín, 2017 to 2018, the study group was consisting of the total of students in 5 th grade school that agreed to participate in the research. The study consisted of 3 stages: a diagnostic which applied a survey where evaluated prior knowledge of the subject; Another intervention to apply the educational program and the end of evaluation where it was confirmed the effectiveness of the intervention. Results were expressed in number and percent being subjected to statistical analysis. Results: 21.7% of students showed insufficient knowledge on the identification of STI, the 79.7% of sexual transmission, the 69.6% If symptoms go to the health center, the 53.6% on delaying the onset of relations sex and the 59.4% the advantages of the use of the condom, which increased after the educational program. Conclusions: applied education program contributed significantly to elevate them knowledge about prevention of sexually transmitted infections and infection per adolescent human immunodeficiency virus.